Pengaruh Financial Distress, Tata Kelola Perusahaan dan Kepemilikan Institusional terhadap Tax Avoidance yang Terdaftar di Bursa Efek Indonesia (Periode 2021 – 2024) - Lhudvia Sekar Pambudi; Arif Makhsun; Endah Yuni Puspitasari (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
Taxes are a primary source of government revenue and play a crucial role in economic development. However, tax avoidance practices are still widely practiced by companies, including in the mining sector, which has significant potential to generate state revenue. This study aims to examine the influence of financial distress, corporate governance (independent commissioners and audit committees), and institutional ownership on tax avoidance in mining companies listed on the Indonesia Stock Exchange for the 2020–2023 period. The study population consisted of 83 companies, and through purposive sampling, 61 companies were selected, with a total of 244 observations. The analysis used panel data regression with the help of Eviews 25. The results indicate that financial distress and institutional ownership have a positive effect on tax avoidance, while independent commissioners and audit committees have a negative effect on tax avoidance. These findings suggest that a company's financial condition and ownership structure play a significant role in determining tax avoidance policies.